Circulating tumor DNA in advanced non-small-cell lung cancer patients with HIV is associated with shorter overall survival: Results from a Phase II trial (IFCT-1001 CHIVA). (July 2021) - Wislez, Marie; Domblides, Charlotte; Greillier, Laurent; Mazières, Julien; Monnet, Isabelle; Kiakouama-Maleka, Lize; Quantin, Xavier; Spano, Jean Philippe; Ricordel, Charles; Fraisse, Philippe; Janicot, Henri; Audigier-Valette, Clarisse; et al.
Highlights: ctDNA detection rates in HIV patients are similar to HIV-undetermined patients. Baseline ctDNA is associated with worse outcome in HIV lung cancer patients. EGFR mutation are less common in this population. Some gene alterations detectable are targetable with specific inhibitors. Abstract: Introduction: HIV is an exclusion criterion for most lung cancer (LC) trials, however LC is the most common non-AIDS-defined malignancy in people living with HIV (PLHIV), poorer prognosis than the general population. Circulating tumor DNA (ctDNA) was a prognostic marker in LC patients from the general population. This study assessed ctDNA's prognostic value in PLHIV from a dedicated phase II trial. Methods: Overall, 61 PLHIV with advanced non-squamous non-small-cell lung cancer (NSCLC) participated in the IFCT Phase II trial evaluating first-line four-cycle carboplatin (Ca) AUC5 pemetrexed (P) 500 mg/m 2 induction therapy every 3 weeks, followed by P maintenance therapy. Blood samples collected before treatment were analyzed to detect ctDNA using ultra-deep targeted next-generation-sequencing (NGS). Results: Appropriate samples were available from 55 PLVIH and analyzed for ctDNA detection. Including 42 males (76.4 %), 52.9 years median age, 51 smokers (92.7 %), five with non-squamous NSCLC Stage III (9%), 50 Stage IV (91 %), and performance status (PS) 0−2. ctDNA was detected in 35 patients (64 %), 22 with high and 13 with low ctDNA levels. Overall, 77 % were positive for TP53, 29 % for KRAS, and 11 % for STK11 mutations, more than one alteration was detected in 43 % of samples. Multivariate analysis showed that positive ctDNA was significantly associated with shorter PFS (HR, 4.31, 95 %CI: 2.06−8.99, p < 0.0001), and shorter OS (HR, 3.52, 95 %CI: 1.72−7.19, p < 0.001). Moreover, OS was significantly longer for patients with low ctDNA levels at diagnosis as compared to high (p = 0.01). Conclusion: We show that ctDNA detection using ultra-deep NGS is an independent prognostic factor in PLHIV with advanced NSCLC.